1993
DOI: 10.1002/bjs.1800800931
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel prolapse and incarceration caused by a vaginal ring pessary

Abstract: A 72-year-old woman was seen in the emergency room with a 2-h history of acute abdominal pain and transvaginal prolapse of the bowel, which had developed immediately after a strong fit of coughing. The patient had undergone transvaginal hysterectomy and colpoperineoplasty 10 years previously for vaginouterine prolapse. A soft rubber vaginal ring pessary of 5.5 cm diameter had been inserted 5 years later because the woman had developed a recurrent rectocystocele but had refused further operation. Periodic follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…39 Several reports implicated pessaries as a causal mechanism for both vaginal and cervical cancer. 25 Chronic inflammation in association with viral infections has been suggested to predispose patients to such cancers as the tumours appeared at the site of pessary placement. 50 It has been proposed that wearing a vaginal ring or cup-and-stem pessary for a long time may cause cancer of the vagina, ulcerative vaginitis, or fistulae.…”
Section: Discussionmentioning
confidence: 99%
“…That patient had rectoand vesico-vaginal ® stulae having neglected a pessary for 18 years. She required extensive surgery and died 8 m onths later.Periodic review does not preclude this complication as seen in our case, and another whereby a ring pessary eroded through the vault in a hysterectomised patient causing small bowel incarceration requiring resection (Ott et al, 1993). She had been followed up periodically with no evidence of erosion prior to presentation.…”
mentioning
confidence: 75%
“…[3][4][5] Rare instances of bowel incarceration through a ring pessary and even cancer of vagina have been reported. 6,7 Vaginal pessary may improve the quality of life but command proper care in elderly patients. Literature lacks adequate consensus on cleanliness or replacement protocols.…”
Section: Discussionmentioning
confidence: 99%